2014
DOI: 10.1103/physrevb.90.054519
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering investigation of the electron-phonon coupling in superconducting Nd(O,F)BiS2

Abstract: We have performed polarized Raman scattering measurements on the newly discovered superconductor Nd(O,F)BiS2 (Tc = 4 K). We observe 2 Raman active modes, with frequencies in accordance with first-principles calculations. One A1g phonon mode at 112.4 cm −1 exhibits a Fano line shape due to electron-phonon coupling. We find a resonance for this mode at 2.45 eV excitation energy. We estimate a 0.68 contribution of this mode to the electron-phonon coupling constant λ. Our Raman results suggest that the BiS2-based … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…However, in our fourcomponent system where CP 3 -skyrmions are formed, one can tune the model parameters u ⊥ , u z to approximately restore the SU(2) symmetry of the valley pseudospin, so as to have a large pseudospin skyrmion, even when the anisotropic energy for both spin and valley pseudospin is high. By analogy, skyrmion also appears in graphene monolayer at ν = 0 when the valley pseudospin SU(2) symmetry or the SO(5) symmetry 46 is approximately restored.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…However, in our fourcomponent system where CP 3 -skyrmions are formed, one can tune the model parameters u ⊥ , u z to approximately restore the SU(2) symmetry of the valley pseudospin, so as to have a large pseudospin skyrmion, even when the anisotropic energy for both spin and valley pseudospin is high. By analogy, skyrmion also appears in graphene monolayer at ν = 0 when the valley pseudospin SU(2) symmetry or the SO(5) symmetry 46 is approximately restored.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…Regarding the mechanisms of superconductivity in the BiCh 2 -based family, the pairing mechanisms of the BiCh 2 -based superconductor family are still controversial 19 , owing to superconducting properties that are tunable by external and/or chemical pressure effects, which sometimes causes scattered results. Although earlier theoretical and experimental studies suggested conventional mechanisms with fully gapped s-wave pairing states [21][22][23] , recent theoretical calculations of T c indicated that a T c of an order of several K to 10 K in BiS 2 -based superconductors with a tetragonal structure cannot be explained within phonon-mediated models 24 . Furthermore, angle-resolved photoemission spectroscopy (ARPES) proposed unconventional pairing mechanisms owing to the observation of a highly anisotropic superconducting gap in NdO 0.71 F 0.29 BiS 2 25 .…”
mentioning
confidence: 96%
“…3(b-d) and 3(e-g) a quantitative analysis of the peak positions and linewidths of the P5, P6 and P7 peaks, which have been fit simultaneously with three Lorentzian functions convoluted by a Gaussian function representing the system resolution. In each case, the peak position ω ph (T ) and the linewidth Γ ph (T ) follows simple expressions corresponding to the anharmonic phonon decay into acoustic phonons with the same frequencies and opposite momenta [15][16][17][18]:…”
mentioning
confidence: 99%